Meminang Pinangan Orang Lain Menurut Kompilasi Hukum Islam dan Ulama Fiqih - Mughni, Syafiq; Fiqoh, Amilatul; Yansa, Fiki Angga; Roikhah, Iva Farikhatur (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2023)
Before carrying out a marriage there are stages in the form of a proposal or it can be called a khitbah. Propose comes from the word Pinang with the verb propose. The equivalent of the word propose is applying and in Arabic is khitbah. Proposal in language is asking a woman to be his wife, both for himself and for others. Khitbah is a statement of the man's desire for a certain woman to marry him and the woman announces this engagement. Proposal is one of the important stages before a marriage is carried out, through a proposal it is hoped that both parties can get to know each other better. Therefore in this article the author will discuss further about the proposal, which aims to provide detailed insight to the reader through the research results of this article